Agility as an innovation driver: towards an agile front end of innovation framework - Brand, Marco; Tiberius, Victor; Bican, Peter; Brem, Alexander (Review of Managerial Science, 2019)
The innovation of products, services, and business models is key to firm survival, performance, and growth in today’s turbulent business environments. However, accelerating environmental dynamics also require speeding up the innovation process. A suitable solution may be the use of agility, especially at the front end of innovation. In this study, we aim to identify agility enablers in this first stage of the innovation process. We follow a two-step procedure. First, we review existing agility frameworks and find that several agility enablers are already discussed, but no holistic framework exists yet. Second, we conduct qualitative expert interviews to obtain a better understanding of additional enablers and enabler attributes. By comparing the theoretical and managerial sources, we find gaps in each side’s attention. As a result, we introduce a novel, agile front end of innovation framework that helps firms pay attention to agility enablers that can speed up the innovation process.<br
Keywords: Agile innovation process Agility framework Front end of innovation Innovation driver Innovation framework

Bayer in India: Intellectual Property Expropriation? - Bican, Peter; Truong, Quynh Nhu (2014)
Bayer Group needed to reassess its strategies regarding intellectual property, as well as its emphasis on research and development. The Indian government had ruled against Bayer by granting a compulsory licence to a local generic drug manufacturer that allowed them to distribute a copy of Bayer’s blockbuster cancer drug at a fraction of the original price. This ruling demonstrated that pharmaceutical innovation could not be effectively protected by conventional intellectual property rights in emerging markets. As a result, the core of the pharmaceutical industry’s business model was called into question: If ideas and inventions could not be protected, was the there any incentive for firms to innovate? Would this victory for generic drug manufacturers trigger similar rulings elsewhere? Would the prevailing patent-centric IP strategies need to be adapted to emerging markets? Or would innovator companies finally have to withdraw from markets with weak IP protectio
Keywords: Intellectual property; innovation; patent strategy; emerging markets; India

Critical success factors in the front end of innovation: Results from an empirical study - Wagner, Simon; Bican, Peter; Brem, Alexander (International Journal of Innovation Management, 2020)
This study empirically analyses the effects of five critical success factors on the front end of innovation and new product development success. Data from a self-developed questionnaire on a cross-industry sample of 77 German-based small- and medium-sized firms were collected through an online survey. Accouting for factors not included in previous studies, the results indicate that strategic alignment, creative encouragement, and external collaboration are the key predictors of front-end success. Surprisingly, the impact of process formalisation and the importance of cross-functional collaboration for front-end success could not be supported. We conject that collaboration in the front end of innovation must exceed simple communication and information exchange to significantly effect front-end success. Managerial implications of this study include the need for an internal search for ideas by fostering employees' creative abilities while simultaneously remaining open to external input. Also, activities in the front end of innovation should be aligned with the organisation's overall business strategy to promote successful ideation.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Front-end of innovation; Innovation collaboration; Innovation management; Success factors

Cross-Border Dynamics of IP Modularity: International Patenting in LEDs and Lithium-Ion Secondary Battery Technology - Bican, Peter; Caspary, Dirk; Guderian, Carsten (Management International Review, 2022)
To profit from their inventions, multinational enterprises rely on various appropriation and internationalization strategies. Intellectual property modularity serves as a reliable option to master the tradeoff between owning the “right” (i.e., valuable) patents in a technology and sharing other “less valuable” patents to spur innovation and foster technology dissemination. Through an inductive, multi-case approach looking at light-emitting diodes and lithium-ion secondary battery technology, we expand prior intellectual property modularity to incorporate internationalization effects across borders. Relying on patent classifications, we trace the development of these two technologies and key multinational enterprises in various countries longitudinally from 1990 to 2018. We introduce the Dynamic IP Modularity Application Matrix and demonstrate that integrating the firm and country levels yields insights into dynamic internationalization developments, particularly when considering the drawbacks to intellectual property modularity. Herein, decision-makers need to secure not only currently valuable but also potentially valuable intellectual property to successfully apply an international intellectual property modularity value capture strategy.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Cross-border development; Intellectual property modularity; Internationalization; Multinational entities; Patents; Technology dissemination

Digital Business Model, Digital Transformation, Digital Entrepreneurship: Is there a sustainable "digital"? - Bican, Peter; Brem, Alexander (Sustainability, 2020)
Digitalization plays a major role in contributing towards the United Nations Sustainable Development Goals. Without transformation of existing businesses, both economic and environmental challenges of the future cannot be solved sustainably. However, there is much confusion on interrelationships and terms dealing with digitization or digitalization: Digital business model, digital transformation, digital entrepreneurship. How do these terms interrelate with and to digitalization, and how do they support firms to grow sustainably? To answer this question, we identified seven core digital-related terms based on a structured literature search within the management and economics domain, namely: Digital, Business Model, Digital Business Model, Digital Technology, Digital Innovation, Digital Transformation, and Digital Entrepreneurship. Thereafter, we analyzed prior literature for deriving a common understanding and definition as a basis for interrelations within a conceptual framework. Definitions were presented in a case study setup with twelve innovation and research and development (R&D) managers from various business units of a German high-tech company. Based on these insights, we propose a conceptual framework on how Digital Readiness, Digital Technology, and Digital Business Models might sustainably relate to Innovation, moderated by a Digital Transformation Process. With this approach, we aim to equip practitioners and researchers alike in handling and addressing change through digitalization sustainably.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Business model; Digital business model; Digital entrepreneurship; Digital innovation; Digital technology; Digital transformation; Digitalization; Sustainable business model

Digital entrepreneurship in finance: fintechs and funding decision criteria - Hommel, Kristin; Bican, Peter (Sustainability, 2020)
After the 2007–08 global financial crisis, research flourished on entrepreneurship through digital innovation in the financial market as well as on investors’ influence on digital technology-based entrepreneurs’ funding decisions. This study combines these two research streams to analyze the decision-making criteria for funding financial technology companies (fintechs), hybrid companies that combine digital entrepreneurship, technology, and banking. The study first uses prior literature to derive important characteristics to define fintechs and then uses 12 expert interviews to elaborate on decision-making criteria in funding. Except for smaller peculiarities, fintech funding does not appear to differ from that of other digital entrepreneurship in different markets, and—as with most digital business models—scalability was identified as a key criterion. Additionally, by serving as a major provider of money for young companies, banks have changed their role and positioning in funding new financial technology entrepreneurs. Through developments in digital technology, banks have shifted from traditional money-lending activities (i.e., debt-financing) to becoming stakeholders in fintechs and, hence, equity investors. We also describe how these formerly distinct fields have converged due to regulatory requirements, digital newcomers, and a need for constant innovation, with their future sustainable development dependent on sharing and collaboration.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Decision criteria; Digital entrepreneurship; Fintech; Funding; Investors; Startups; Success factors; Venture capital

Digital platform-based business models – An exploration of critical success factors - Rohn, Daniel; Bican, Peter; Brem, Alexander; Kraus, Sascha; Clauss, Thomas (Journal of Engineering and Technology Management, 2021)
Recent digital transformation initiatives facilitate the access to platform-based business models on the demand side as well as enabling the necessary proximity to potential customers on the supply side. Due to this network connectivity between people, organizations, resources and entire industries, value and economic growth can be generated within the interactive ecosystem of digital platforms. The special feature of this business model is that competitive advantages, contrary to dominant paradigms, do not primarily rely on the physical infrastructure or the control over scarce and valuable resources. Despite the high practical relevance, little systematic knowledge exists on why platform-based business models often outperform traditional pipeline businesses in many respects. We contribute to this research gap by exploring the critical success factors of platform business models. Based on a qualitative analysis on digital platforms in the metal and steel industry, we identify six key success factors of platform-based business models: We relate these success factors to the design of the three dimensions of business models as described in the literature: (1) value creation, (2) value delivery, and (3) value capture dimensions. Furthermore, our analysis could extend these and design features of the business model by three additional success factors (4) the promotion and sensitization of digital transformation, (5) a suitable platform architecture and strategic judgement of platform providers, as well as (6) the promotion of a start-up culture as central success factors.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Business model; Digital business model; Digitalization; Platform; Qualitative analysis; Steel industry; Success factors

Digitizing Grocery Retailing: The Role of Emerging Technologies in the Value Chain - Weyer, Julia; Tiberius, Victor; Bican, Peter; Kraus, Sascha (International Journal of Innovation and Technology Management, 2021)
Multiple emerging technologies both threaten grocers and offer them attractive opportunities to enhance their value propositions, improve processes, reduce costs, and therefore generate competitive advantages. Among the variety of technological innovations and considering the scarcity of resources, it is unclear which technologies to focus on and where to implement them in the value chain. To develop the most probable technology forecast that addresses the application of emerging technologies in the grocery value chain within the current decade, we conduct a two-stage Delphi study. Our results suggest a high relevance of almost all technologies. The panel is only skeptical about three specific projections. As a consequence, grocers are advised to build up knowledge regarding the application of these technologies in the most promising areas of their value chain. © 2020 World Scientific Publishing Company.
CRIS-Team Scopus Importer:2021-05-14
Keywords: artificial intelligence; augmented reality; big data analytics; blockchain technology; Delphi study; drones; grocery retailing; RFID; technological forecasting

Distinguishing Self-Sufficient Business Incubators in Start-up Incubation Ecosystems - Straub, Oliver; Bican, Peter; Brem, Alexander (Research Handbook on Start-Up Incubation Ecosystems, 2020)
Prior literature analysed why incubators exist and how to differentiate the various incubator types. However, measures that lead incubators to run as independent, self-sufficient incubation ecosystems (i.e. without the dependence on subsidies) remain largely absent. Based on a survey with 71 incubators, our results implied differences between the two groups in regard to their business models, with indications of significant differences in the customer value proposition, the profit formula, as well as the key resources and processes provided. The findings support previous claims regarding the need for a profit driven nature, regardless of business profit orientation, as well as generating diverse income streams to cover operational costs. Moreover, new insights on key elements of incubators’ business models within start-up incubation ecosystems are presented. With this chapter, practitioners as well as researchers will gain a further understanding of the success factors of self-sufficient incubators that contribute to functioning incubation ecosystem
CRIS-Team Scopus Importer:2024-12-16
Keywords: Entrepreneurship; Incubation Ecosystems; Financial Performance; Investors

Effectuation vs. Causation: Can established firms use Start-Up Decision-Making Principles to stay innovative? - Henninger, Pascal; Brem, Alexander; Giones, Ferran; Bican, Peter; Wimschneider, Christine (International Journal of Innovation Management, 2019)
More and more, established companies try to cooperate with start-ups, build their own, or try to imitate their mindsets. But, do they make decisions like expert entrepreneurs? Effectuation theory describes entrepreneurial decision-making, it has been popular in entrepreneurship research for the last two decades, but still underexplored in contexts such as established company’s decision-making. Therefore, this study answers the question of which factors affect the use of effectuation in established companies. Furthermore, the current use of the start-up decision-making principle is investigated. The research results show a higher use of effectuation over causation (alternative mechanism) in established companies. However, decision-making principles like “Mean orientation” and “Contingency orientation” are still dominated by causation. Identified factors for implementing effectuation in established companies are divided into six categories. In particular, effectuation requires a high flexibility and willingness to change goals. Using the already available means and resources of a company to pursue new goals, is another argument for using effectuation. Additionally, a more open and transparent culture, encouraging the identification and admittance of mistakes, also supports the use of effectuation. Based on this research, established companies should be able to understand better on which factors the implementation of effectuation depends and where it makes sense to use it.<br
Keywords: Effectuation; causation; decision-making principles; uncertainty; established companies; means orientation; affordable-loss orientation; contingency orientation

Forschungsförderung von kleinen und mittleren Unternehmen: Begrifﬂichkeiten und sachgerechte Abgrenzung - Brem, Alexander; Bican, Peter (Wirtschaftsdienst, 2017)
Keywords: F&E Management; Forschung und Entwicklung; KMU; SME; Forschung; Forschungsförderung

Gender Differences in Technology and Innovation Management - Insights from Experimental Research - Brem, Alexander; Bican, Peter; Wimschneider, Christine (Degruyter, 2020)
Even though the number of working women has steadily increased over the last few years, women are still significantly under-represented in STEM activities (i.e. mathematics, informatics, science and technology). In order to eliminate this under-representation, numerous education policies and corporate initiatives, particularly in the recent past, have been aimed at increasing women's enthusiasm for STEM activities and professions. According to the latest surveys, however, it is clear that these efforts have not yet led to the desired success. Compared to their male counterparts, women continue to do fewer STEM activities. One possible reason for this is that relatively little is yet known about the concrete impact of the above education policies on working with innovation and technology: What are the gender differences between women and men? Is it enough to recognize these differences, or should these differences ideally not only be recognized, but also treated appropriately or even encouraged? This anthology deals with current topics in technology and innovation management against the background of these and other gender-relevant aspects. Empirical analyses and experiments in collaboration with companies from various sectors provide a sound scientific basis on which new results and findings are presented: How do women and men deal with creativity and competition? How are technologies applied and how can differences in access to technology be deduced? Answers to these and other questions help decision-makers in politics and business to proactively use the differences between women and men to motivate women to work in the STEM field and to strengthen them by acknowledging existing difference
Keywords: Gender

Gender Diversity Effects in Investment Decisions - Hohl, Lennard; Bican, Peter; Guderian, Carsten; Riar, Frederik J. (Journal of Entrepreneurship, 2021)
This study examines the gender gap in investment decisions in a prominent setting: the American TV show Shark Tank. Our study is based on a sample of 895 pitches from 10 seasons comprising 222 episodes from 2009 to 2019. Contradicting prior research, our findings suggest that female entrepreneurs are not discriminated against in pitch success rates, independent of their respective industrial settings. We find that the valuations from the entrepreneurs themselves (males overvalued their ventures by 57.19%) and final deal valuations (male deals were overvalued by 50.50%) are significantly lower for females, hinting towards a self-imposed gender gap in entrepreneurship and angel investing. As the gender gap in entrepreneurship and angel investment seems to result from a lower rate of entrepreneurial intentions by women, we suggest fostering female entrepreneurship by raising the number of female entrepreneurs and business angels who may serve as role models among those potential female entrepreneurs and business angels at the brink of becoming actual entrepreneurs, as demonstrated in Shark Tank. Particularly, in teams, mixed founder teams consisting of males and females may support the creation of promising start-ups with viable business models.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Entrepreneurship; gender differences; gender gap; investment decision-making; investor pitch; Gender

HKS-Dessous: A Main Street Retail Entrepreneur Handling Digital Change - Tiemer, Johannes; Guderian, Carsten C.; Bican, Peter (2017)
Late in 2016, the owner of a lingerie business in Düsseldorf, Germany, faced a series of questions regarding the health of her business in a changing environment. The German retail environment had traditionally consisted of many specialized (often family-owned) small- to medium-sized retailers, and many of these stores had not kept pace with globalization and the digital revolution; market changes and increasing competition forced them to close. Other main street retailers managed to grow in these challenging environments, overcoming and moving in front of their previous competitors. HKS Wäsche & Dessous was one of those independent retailers. How could the owner of such a business continue to cope with the changing business environment? How could she deal with the digital revolution or even turn it to her advantage? What can entrepreneurs do to maintain and even develop their businesse
Keywords: Small- to medium-sized enterprises; hidden champion; growth; business model innovation; change management

HOW CAN the LEAN STARTUP APPROACH IMPROVE the INNOVATION PROCESS of ESTABLISHED COMPANIES? AN EXPERIMENTAL APPROACH - Scheuenstuhl, Felix; Bican, Peter; Brem, Alexander (International Journal of Innovation Management, 2021)
The Lean Startup approach and its related Minimum Viable Product thinking is one of the key trends not only in entrepreneurship, but also in more and more established companies. Before this background, this paper experimentally investigates whether and how the Lean Startup approach improves innovation processes in established companies. For this, the overall experiment had 23 participants, the outcome was then matched against a control group and evaluated through a survey with 146 representatives of the target group of the product. The results show that the Lean Startup approach outperforms the traditional approach and that this method improves the success rate of innovation ideas and thus supports the learning philosophy within established companies. Moreover, the experiment revealed a superior performance, especially relating to financial output. Based on these results, implications for research and companies are discussed, as well as limitations and further research suggestions.
CRIS-Team Scopus Importer:2021-05-21
Keywords: innovation management; innovation process; innovation success; Lean startup; minimum viable product

Influential factors of network changes: Dynamic network ties and sustainable startup embeddedness - Keidel, Julia; Bican, Peter; Riar, Frederik J. (Sustainability, 2021)
This research investigated influential factors on changes in networks of startups through a qualitative exploratory case study approach. Based on interviews with founders in Germany and selected stakeholders in entrepreneurial networks combined with a network mapping approach, we developed a framework of influential factors on network changes. In essence, this framework categorizes factors into sustainable resource acquisition, knowledge and skill acquisition, interpersonal factors, and interorganizational factors. Overall, our research contributes to a better understanding of factors that impact network changes by providing a construct with potential for theoretical standardization. In addition, this research offers important managerial implications.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Entrepreneurial firm; Entrepreneurship; Influential factors; Network; Network changes; Relationships; Startup; Ties

Innovation management in crisis: patent analytics as a response to the COVID-19 pandemic - Guderian, Carsten; Bican, Peter; Riar, Frederik J.; Chattopadhyay, Sarbani (R & D Management, 2020)
Crises like the COVID-19 pandemic affect firms’ innovation management and decision making. On the downside, crises lead to detriments like budget constraints, to which firms often respond by reducing their innovation activities. On the upside, crises are opportunities, where some firms exploiting changing market requirements and necessities excel. No matter in which direction, decision makers must react quickly but often rely on ad-hoc decisions or even gut feeling when drafting their crisis response strategies. Through a series of distinct cases, we demonstrate that innovation management may fill this void through patent analytics. Drawing on biochemical expertise, we particularly describe the functions and effects of COVID-19. To counter downside detriments, firms may circumvent budget constraints by discerning patents that can be (1) monetized, for example via sales or licensing deals, or (2) abandoned to achieve cost-savings, allowing firms to maintain their innovation activities. To realize upside opportunities, firms and governments may use patent analytics to detect key biotechnology firms that are likely to successfully develop treatments and vaccinations against pandemics like COVID-19. Promulgated U.S. interest in relocating foreign firms to the United States is not without technological and commercial reasoning. Herein, the insights of this study contribute to a better understanding of the use of patent information, such as smart patent indicators, harmonized patent data, novel annuity fee measures, and hand-collected datasets of COVID-19 and related antibodies’ patents to the management of innovation in times of crisis.
CRIS-Team Scopus Importer:2020-12-25

It wasn't me: Entrepreneurial failure attribution and learning from failure - Riar, Frederik J.; Bican, Peter; Fischer, Jannes (International Journal of Entrepreneurial Venturing, 2021)
Can entrepreneurs learn from failure? Using frameworks from attribution theory, we draw on unique qualitative data from entrepreneurs who had experienced failure before re-engaging in entrepreneurial activities. We find that the direction of failure attribution, as either attributed to external or internal causes, affects learning from failure differently and propose that while an excessive focus on self-attribution may harm future prospects of entrepreneurial activity, over-attributing failure to external causes might possibly hinder positive returns from learning from failure. Moreover, external and internal aspects influence how entrepreneurs learn from previously failed ventures. Failure shall not be romanticised, as it entails profound consequences for attribution and its effects on learning. Implications for research on failure, learning from failure, and attribution theory, as well as implications for practice are further discussed. Propositions for future research endeavours are derived.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Attribution; Entrepreneurial failure; Entrepreneurship; Learning from failure; Self-attribution; Start-ups

Managing innovation performance: Results from an industry-spanning explorative study on R&D key measures - Bican, Peter; Brem, Alexander (Creativity and Innovation Management, 2020)
Research on R&D performance measures applied in firms is still scarce. Based on the established "R&D laboratory as a system" thinking, systematically derive and identify R&D department level key performance measures. Through a mixed-method approach, grounded in (1) literature and (2) text analysis, 154 R&D performance measures were developed. Amongst those, an (3) online expert survey, as well as (4) three independent focus group workshops with >40 industry experts from more than ten industries identified and validated ten key R&D performance measures. All industry experts involved are members of an innovation network, additionally accounting for innovation network effects. In contrast to earlier research, some of the measures like degree of anticipation of internal customer needs were perceived both by the survey respondents and the focus groups as key measures, indicating that behavioral measures should not be excluded per se. However, the importance of external validity of R&D performance or indicators to measure performance in relation to activities outside the R&D department were not confirmed. Hence, we partly confirm the relevance of the original "R&D Lab" measures, contributing a more granular level, thereby drawing implications for future research and practice.
CRIS-Team WoS Importer:2020-05-19

Managing Knowledge in Open Innovation Processes: An Intellectual Property Perspective - Bican, Peter; Guderian, Carsten C.; Ringbeck, Anne (Journal of Knowledge Management, 2017)
As firms turn their innovation activities toward collaborating with external partners, they face additional challenges in managing their knowledge. While different modes of intellectual property right regimes are applied in closed innovation systems, there seems to be tension between the concepts of “open innovation” and “intellectual property rights”. The purpose of this paper is to investigate how firms best manage knowledge via intellectual property rights in open innovation processe
Keywords: Intellectual property; Knowledge management; Open innovation; Patents; Innovation process; Success drivers

Martin Bauer Group: Corporate Social Responsibility with EinDollarBrille - Guderian, Carsten C.; Bican, Peter (2016)
In the fall of 2013, the family-owned Martin Bauer Group, a German-based company and world leader in the business-to-business market for tea and herbal extracts, became interested in the idea of collaborating with the frugal innovation company EinDollarBrille (OneDollarGlasses). The Martin Bauer Group was engaged in multifaceted corporate social responsibility activities, both domestically and abroad. Specifically, it fostered the development and diffusion of frugal innovations, which were affordable products or services developed under strict financial constraints to cater to low-income individuals in emerging markets. These companies usually worked in collaboration with partners. One such frugal innovation company, OneDollarGlasses, created durable, yet affordable, eyeglasses for people in the African country of Sudan, a prime sourcing market for the Martin Bauer Group. The work of OneDollarGlasses illustrated the reasons, motivations, and challenges that innovators often faced within developed and emerging markets when engaging in corporate social responsibility activities. Should The Martin Bauer Group work with OneDollarGlasses? Could the company be helpful and make a meaningful difference to the people in emerging markets by collaborating with frugal innovators like OneDollarGlasses? What benefits would there be for the Martin Bauer Group if they do?
Keywords: CSR; family firms; emerging markets; der Mittelstand; eye care; clinical services; glasses; innovation; roleplay; dialogue; non-profit; NGO; public relations

Organizational ambidexterity and competitive advantage: The role of strategic agility in the exploration-exploitation paradox - Clauss, Thomas; Kraus, Sascha; Kallinger, Friedrich Lukas; Bican, Peter; Brem, Alexander; Kailer, Norbert (Journal of Innovation & Knowledge, 2020)
Attaining competitive advantage is especially crucial for innovative firms. Due to increased competition, firms employ various types of innovation activities to position themselves against their competitors. Ambidexterity and strategic agility have been found to strengthen this position. Whereas scholars analyzed strategic agility's and ambidexterity's impact on organizational performance, ambidexterity's impact on the competitive advantage of organizations remains largely unexplored. Tensions between exploration and exploitation within an ambidextrous strategy make it difficult to reap benefits in establishing competitive advantage. Contrary, strategic agility centers on organization's capacities to quickly respond to shifting demand, hence, increasing its competitive advantage. Through a mixed-method approach, comprising of a literature review and quantitative analyses of 150 German mid-sized firms in the engineering industry, it is demonstrated how ambidexterity, exploration and exploitation, in conjunction with strategic agility, affect the competitive advantage of firms. In order to sustain, firms should either favor an exploration strategy of innovation processes to come up with radically new knowledge, products and services, or combine an exploitation strategy with strategic agility. A strategy of sole exploitation is not beneficial towards increased competitive advantage, while an ambidextrous strategy seems to even negatively influence the competitive advantage of a firm.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Ambidexterity; Competitive advantage; Firm innovation; Strategic agility; Strategy

Patents and Sustainable Medical Treatment in Developing Countries: Lessons from COVID-19 Vaccines - Demir, Ezgi; Bican, Peter (Sustainability, 2023)
COVID-19 has had devastating effects worldwide, and vaccines have become the most efficient solution to address the current pandemic situation thus far. After COVID-19 vaccines had been developed, discussions of the various countries' equality of access gained traction, with patents and pricing forming a significant part of this discourse. Therefore, this study investigates the impact of patents and prices on the accessibility of COVID-19 vaccines in the developing world, using semi-structured interviews with subject-matter experts in this area of focus. Our analysis of these interviews highlights the fact that patents and prices are not the major barriers to accessibility for medical treatments, both generally and specifically in terms of COVID-19; rather, these barriers relate to the lack of local production capacity, technology transfer, infrastructure, local regulations, and supply-chain competencies. These results suggest that rather than focusing on patents and prices, governments should invest more time in improving technology transfer and using compulsory licenses as a negotiation tool. Moreover, the results show that the pricing strategies applied by companies could have different impacts on access, as could accessibility programs such as COVAX.
CRIS-Team WoS Importer:2023-03-24
Keywords: COVID-19 pandemic; patent; intellectual property; vaccines; developing countries; sustainable medication; sustainability; healthcare; Inklusion

Pioneer or follower: Which strategy to choose? - Dreiling, Aleksej; Bican, Peter (Taylor and Francis, 2022)
CRIS-Team Scopus Importer:2022-09-30

Sustainability meets agile: Using Scrum to develop frugal innovations - Endres, Miro; Bican, Peter; Wöllner, Theresa (Journal of Cleaner Production, 2022)
With the climate crisis looming, innovations are no longer judged by their technical prowess alone but also on their sustainability. Frugal innovations have attracted significant attention in this regard. These user-friendly, cost-effective, and resource-efficient solutions of appropriate quality provide significant value to users and end customers and present attractive solutions to meet the current demands. Nevertheless, knowledge about the development of frugal solutions is scarce. Scrum is one of the most popular agile frameworks and is increasingly implemented in diverse companies' product development processes, although the relationship between Scrum and frugal innovation has not yet been investigated. Based on semi-structured expert interviews with Scrum practitioners, this paper provides the first insights into developing frugal innovations with Scrum. Interviewees generally considered Scrum's impact to be positive, and they named developing a user-friendly solution of appropriate quality as the frugal-innovation characteristic most benefited by applying Scrum. However, Scrum's impact was not explicit on the developed product's price-performance ratio, one of the variables to measure customer value. Therefore, this paper proposes integrating the user perspective into the Scrum process by identifying the actual users of the developed solution and by formally and regularly inviting them to sprint review meetings. To keep the development process efficient while addressing the identified stakeholder needs, organizations should work with fully dedicated, generalist Scrum teams that are knowledgeable on user experience. Additionally, Scrum team members should regularly share their insights gained with marketing departments to improve the effectiveness and appropriateness of pricing decisions. Companies can also address cost-effectiveness and sustainable resource efficiency by developing resource-efficient increments and by reusing existing components. Our study indicates that sustainability efforts, like reaching the UN Sustainable Development Goals, can profit from including agile frameworks in innovation activities.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Agile frameworks; Constrained-based innovation; Frugal innovation; Scrum; Sustainability; Inklusion

Techno-Economic Evaluation of Strategic Solutions to Extend the Range of Electric Vehicles - Weigelt, Michael; Mayr, Andreas; Masuch, Michael; Batz, Kilian; Franke, Jörg; Bican, Peter; Brem, Alexander; Russer, Johannes A.; Russer, Peter (8th International Electric Drives Production Conference (EDPC), 2018)

Techno-Economic Evaluation of Technological Alternatives to Extend the Range of Electric Vehicles - Weigelt, Michael; Mayr, Andreas; Kühl, Alexander; Batz, Kilian; Bican, Peter; Russer, Johannes A.; Russer, Peter; Franke, Jörg (5th Annual Conference on Electric Roads & Vehicles, 2018)

Value Articulation: A Framework for the Strategic Management of Intellectual Property - Conley, James G.; Bican, Peter; Ernst, Holger (California Management Review, 2013)
This article introduces a framework that helps to assimilate intellectual property management activities with the practices of marketing and strategy. With the framework, the management of IP rights is explained within marketing constructs such as the unique selling proposition. The article presents case studies that explore the applicability of the framework in a diversity of industry contexts and firm sizes.
Keywords: Intellectual Property; Licensing; Brand Equity; Patents; Strategic Management; Marketing; Product Life Cycle; Case Method; Value Transference; Multiple Industries

When entrepreneurship meets finance and accounting: (non-)financial information exchange between venture capital investors, business angels, incubators, accelerators, and start-ups - Bratfisch, Clara; Riar, Frederik J.; Bican, Peter (International Journal of Entrepreneurial Venturing, 2023)
Building on qualitative data from 53 interviews with different types of investors and start-ups, we study the financial and non-financial information that different investor types demand to monitor their portfolio start-ups' performance during different lifecycle stages, as well as how entrepreneurs generate and furnish the required information. We specifically show in detail how investors, like venture capitalists, incubators, or business angels, mitigate agency conflicts through the exchange of specific financial and non-financial information, both formally and informally. By directly comparing both investor and investee cases, we provide insight into the monitoring methods common among different investor types and start-ups. While investors consider accounting to be an important part of the relationship, some entrepreneurs do not or set their priorities differently. Our study illustrates that accounting not only plays a crucial role in the management of established businesses, but is equally important in entrepreneurial investment settings, as is financial literacy.
CRIS-Team WoS Importer:2023-03-31
Keywords: Kulturelle Vielfalt

WIPO Study on Patents and the Public Domain (II) - Impact of Certain Enterprise Practices - Conley, James G.; Bican, Peter; Wilkof, Neil (2013)
This study analyzes the relationship at the micro level between the patent system and the public domain, building upon the findings of the Study on Patents and the Public Domain (I).3 It seeks to enhance the understanding of the impact of certain enterprise practices in the field of patents on the public domain and on the important role of a rich and freely accessible public domain. The discussion herein is not focused on the legal and normative aspects of patents and the public domain, but rather on how the intersection of patents with the public domain impacts on patent practice and commercialization. This study explores the effect of the patent regime over time on the existence of a rich and growing public domain. By integrating data from professional and scholarly literature, WIPO and OECD reports, as well as data from both public and subscription sources, the practices and business models of firms such as non-practicing entities are described. The patent management and prosecution techniques of patent owners are then reviewed. Throughout the review, the effect of enterprise practices on the public domain is discussed.
Keywords: Intellectual Property; Patent; Trademark; Copyright; Urheberrecht; Markenrecht; Public Domain; WIPO